Efecto del uso de harina de aguacate en la alimentación de cerdos en la etapa de crecimiento - Bustamante Torres, Gilbert Junior (2024)
This document addresses the inclusion of avocado flour in the diet of pigs in the growth stage, highlighting its significant impact on the development and quality of pork. The research focuses on the use of discarded avocados, transforming them into flour as an innovative strategy. sustainable and nutritious. The use of avocado flour in pig nutrition improves the quality of fatty acids in their muscle tissues, favors digestive health and general well-being. In some studies, animals that consumed this diet experienced an increase in their body mass, greater efficiency in the performance of nutrients and an increase in their activity level, which indicates possible anti-inflammatory and antioxidant effects of avocado flour. Furthermore, a significant change in gene expression related to lipid metabolism and development was observed. The results of this bibliographic research highlight the potential of avocado flour as a nutritional food in pig farming, due to its advantages in both health and animal growth, as well as contributing to a more ecological and sustainable production. Additional research is recommended to explore the different mechanisms behind the benefits and realize their long-term profitability.